2023
DOI: 10.3390/app13179828
|View full text |Cite
|
Sign up to set email alerts
|

A Runway Overrun Risk Assessment Model for Civil Aircraft Based on Quick Access Recorder Data

Xiuyi Li,
Lin Zhang,
Jiaxing Shang
et al.

Abstract: The quick access recorder (QAR), as an airborne device used to monitor and record flight parameters, has been widely installed on various types of aircraft. Based on QAR data, research on runway overrun, a typical flight safety incident, has attracted widespread attention in recent years. However, existing runway overrun risk models generally suffer from oversimplified risk metrics or insufficient consideration of risk dynamics. In this paper, we propose a new dynamic runway overrun risk assessment model based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…They found that flare operations have a significant impact on landing distance and vertical landing acceleration. Li et al [8] proposed a landing trajectory correction method that integrates ground speed and runway position information. They established a dynamic off-runway risk assessment model based on QAR data, uncovering key factors related to off-runway risk during the landing phase.…”
Section: Runway Excursionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that flare operations have a significant impact on landing distance and vertical landing acceleration. Li et al [8] proposed a landing trajectory correction method that integrates ground speed and runway position information. They established a dynamic off-runway risk assessment model based on QAR data, uncovering key factors related to off-runway risk during the landing phase.…”
Section: Runway Excursionmentioning
confidence: 99%
“…Another category of research focuses on the analysis of exceedance events and the study of distances and landing trajectories in runway excursions based on Quick Access Recorder (QAR) data [7][8][9]. In the context of runway excursion research, there has been limited utilization of QAR data for operational risk analysis.…”
Section: Introductionmentioning
confidence: 99%